The prisioner of women prevention to DST help and pregnancy in context of a pratriarchal society - Giordani, Annecy T.; Bueno, Sônia M.V. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Foundations: Toe number of women infected by the HIV-aids in Brazil. It is increasing mainly. duelo sexual relationships with partners hetero or bisexual. ln our patriarchal society, lhe sexuality show off framed in lhe line of lhe gender relationships, where the man usually commands, lllking lhe initiative and determining conducts. wilhout considering the panner’s heahh and lhe children. Objectlves: To correlate the vulnerality of lhe prisioner of women 10 lhe STD-aíds wilh gender relationships inside and out of lhe prison, lifting your perceptions on lhe own sexuality and risks to the STD-aids: 10 guide as for the importance of lhe practice of the safe sex and negotialion with the partner 10 use lhe preservative. Method: we worked 14 the prisioner of women in chain of lhe interior from São Paulo. majorily arnong 1810 34 years, molhers, 2 homosexuals, majority in prision by traffic of drugs. We developed research action humanist. participative and qualillltive, wilh individualized interview and recordings in ribbons K-7 aulhorized, transcription, analysis and interpretalion of lhe speeches. Results: 8 women pointed your partners, as dominanl in lhe sexual relationship and owners of the initiative. Toe tolality almost mentioned sexual freedom with your pair and prevenlion of lhe pregnancy, using different melhods. Mosl never took precautions agains1 the STD-aids. Conclusions: Toe discoveries confirm the results of other pertinent studies 10 women. The vulnerability 10 the infection for HIV and STD. 1ends the gender relalionships. as guide element 10 lhe practices of preventive educatíon.